Energy requirement assessment of bioenergy combine scenarios for cellulose based biofuel production : Version 1.0 - Perrino Martin, Elena (SLU/Dept. of Energy and Technology, 2012)
Second generation biofuels are a good alternative to replace fossil fuel in the transport sector, such as ethanol production from lignocellulose. The technology is not working at full scale yet, partly due to high investment costs. To reduce these costs, one possibility is the integration of ethanol production in a combined heat and power plant (CHP).